Statistical Comparison to Determine First Line Regimen of Two Anti-Malarials for Uncomplicated Plasmodium Falciparum Malaria among Children Under 5 Years - Alnory, Ahmed; Abdalla, Sondous A (Edelweiss Applied Science and Technology, 2018)
Comparison of regimen efficacy in clinical medicine has been utilized to improve the effect of drugs against disease The pairs alternative t-test method approach is used in this experimental study to derive efficacy estimates of two anti-malarial regimens. This study aimed at comparing mostly used drugs against malaria in Africa in the present time, namely artesunate-mefloquine and artemether-lumefantrine to determine which of them is more effective treatment of the disease among children under 5 years of age and thus may be considered as a first line treatment, especially when laboratory tests are not available. The results achieved in this study were based on hypothetical experimental data. The data which represented 12 pairs of matches children were analyzed using t tests with the help of SSS program. The study concluded that artesunate-mefloquine is more effective as a first line treatment than artemether-lumefantrine in children less than five years age of both sexes.